Analysis of Electropherogram Profile of Crude Cartilage Oligomeric Matrix Protein for Rheumatoid Arthritis Diagnosis - Nyi Mekar Saptarini, Marlia Singgih Wibowo, Ihsanawati, Tutus Gusdinar (Journal of Applied Pharmaceutical Science, 2017)
Cartilage oligomeric matrix protein (COMP) is a potential biomarker to monitor the development of cartilage damage and injury in rheumatoid arthritis (RA). The most accurate method of determining COMP levels is the enzyme-linked immunosorbent assay, but this method is expensive and requires trained analysts. An alternative method to solve this problem is analyzing the electropherogram profile of crude COMP. This method separates proteins based on molecular weight, so it can differentiate pentamer COMP from its fragments. This study was conducted to analyze the electroferogram profile of crude COMP of RA patients and normal individuals, so it can be applied to RA diagnosis. COMP was precipitated on its isoelectric pH, then crude COMP was dissolved and electrophoresed by sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE).The electropherogram profiles of RA patients were dominated by pentamer and dimerbands, whereas the electropherogram profiles of normal individual were dominated by tetramer, trimer, and dimer bands. Increased pentamer COMP in serum was indicated by the cartilage damage. The electropherogram profile of crude COMP of RA patient can be differentiated from normal individuals, so it can be used for the RA diagnosis.
Keywords: Serum, Crude COMP, Precipitation, Isoelectricp H, SDS-PAGE.